Evaluation of the clinical practices and awareness of hematologists related to hepatitis B reactivation - Colkesen, Fatma; Yilmaz, Seda; Duran, Mustafa (Annals of Medical Research, 2022)
Aim: This study aimed to evaluate the awareness and knowledge of hematologists about hepatitis B virus reactivation (HBVr) to draw attention to this subject's importance. Material and Methods: Sixty-six hematologists included in Turkey. A 13-item questionnaire was administered to the study group to evaluate awareness, knowledge, and experience of HBVr. Results: It was thought by 97% of the participants that all patients who were to receive immunosuppressive treatment (IST) should be screened in respect of HBV. While 98.5% of the hematologists thought HBsAg should be examined in the screening, 89.4% thought anti-HBcIgG should be examined. A total of 89.4% of the hematologists stated that prophylaxis should be started before IST. HBV prophylaxis had been previously administered to patients receiving IST by 97% of the hematologists, and 44% had encountered HBVr at least once in patients. Training related to HBVr after IST had been received following graduation by 75.8% of the hematologists. Conclusions: Awareness about HBVr was found to be high in the hematologists in this study. However, it is worrying that there are clinicians not using anti-HBcIgG test in screening, and the screening rate before treatment with tyrosine kinase inhibitors was low. There was seen to be no standard follow-up protocol either for patients who had started or had not started prophylaxis. This study can be considered to be a stimulus on the subjects of preventing patients with isolated anti-HBcIgG positivity being overlooked, determining the HBVr risk associated with IST, and optimizing the follow-up of patients.
Keywords: Hematologist; hepatitis B; immunosuppressive treatment; reactivation